Method for preparing all-solid-waste-based non-sintered ceramsite by synergistically recycling solid wastes
By combining fly ash in thermal power plants, blast furnace granulated slag, flue gas desulfurization gypsum and water-eluted chlorine-free domestic waste incineration fly ash, alkali-activated gelling materials without admixtures were prepared, which solved the problems of high energy consumption and carbon emissions when dealing with fly ash incineration in the existing technology, and achieved high-strength, low-cost, and environmentally friendly preparation of all solid waste-based burn-free ceramic pellets.
Patent Information
- Application Number
- CN202411883023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems of high energy consumption, carbon emissions and environmental pollution when dealing with domestic waste incineration fly ash, and the cement-based curing/stabilization system has limitations when dealing with waste incineration fly ash with high heavy metal content.
By combining four solid wastes: fly ash in thermal power plant, blast furnace granulated slag, flue gas desulfurization gypsum and water-eluted chlorine fly ash, alkali-activated gelling materials without admixtures are prepared, and high-strength all-solid waste-based burn-free ceramic granules can be prepared for a few days of natural curing at room temperature.
The preparation of all solid waste-based burn-free ceramics with low cost, low energy consumption and no carbon emissions can effectively cure heavy metals in the incineration fly ash of dechlorinated domestic waste, and truly achieve the purpose of environmental protection.
Smart Images

Figure CN119707334A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing ceramsite, and in particular to a method for preparing all-solid waste-based unburned ceramsite by co-recycling solid waste, specifically a method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes. Background Art
[0003] Fly ash is particulate matter and flue sediment captured in the flue gas purification system of waste incineration. It contains 5% to 10% heavy metals (such as lead, cadmium, copper, zinc, etc.) and high concentrations of chloride ions (10,000 to 30,000 mg / kg). Therefore, it is easy to catalyze and enrich PCDD / Fs in domestic waste incineration plants, and dioxin pollutants with a toxic equivalent (TEQ) of up to tens of nanograms can be detected. Due to its toxicity, the "National List of Hazardous Wastes (2021 Edition)" lists fly ash as hazardous waste HW18, and stipulates that fly ash must be solidified / stabilized and meet safety standards before entering the landfill for zoned landfill.
[0004] To date, the main methods for treating MSWI fly ash include chemical stabilization, sintering, melting solidification, cement rotary kiln co-processing, and cement-based solidification / stabilization (S / S) treatment. However, it is difficult for a single chelating group of chemical stabilization to simultaneously block multiple types of heavy metals. Although sintering and melting can effectively block toxic pollutants, their high energy consumption and flue gas treatment costs caused by volatile heavy metals (such as Pb, Cd, and Zn) limit their widespread application. In contrast, cement-based solidification / stabilization is an economical and widely used technology that locks toxic components in the cement matrix through physical and chemical fixation. Municipal solid waste incineration fly ash is rich in inorganic and organic chlorine from high-salt kitchen waste and PVC plastic waste, and the high chloride characteristics of fly ash will weaken the durability and strength of the material, making it difficult to meet the quality requirements of construction projects. GB175-2007 "General Portland Cement" requires that the chloride ion content in the raw materials is ≤0.06%; HJ662-2013 "Technical Specifications for Environmental Protection of Co-disposal of Solid Waste in Cement Kilns" requires that the chloride ion content in the kiln materials is ≤0.04%. Therefore, the fly ash from incineration must be dechlorinated before it can be added to the cement raw materials. At present, the main method in engineering to reduce the high liquid-solid ratio is to increase the number of washing times in order to achieve a better fly ash washing dechlorination effect and reduce the subsequent washing wastewater treatment load as much as possible, such as the three-stage countercurrent washing process. However, the cement-based solidification / stabilization system has certain limitations in treating waste incineration fly ash with high heavy metal content. At the same time, cement production itself also brings about environmental pollution, mineral resource consumption and high carbon emissions.
[0005] The ultimate way out for the harmless disposal of fly ash from the incineration of domestic waste is sanitary landfill and resource utilization. The former mainly focuses on the solidification / stabilization of heavy metals, while the latter mainly uses the original / pretreated fly ash for secondary building materials. In contrast, the use of secondary building materials and resource disposal methods can have a stronger ability to solidify and stabilize heavy metals in fly ash from the incineration of domestic waste. And the recently issued "Technical Specifications for Pollution Control of Fly Ash from Incineration of Domestic Waste (Trial)" (HJ1134-2020) has made fly ash resource utilization have a policy basis. Therefore, it is necessary to develop a low-carbon, economical, efficient and environmentally friendly immobilization material. Alkali-activated gelling materials have the advantages of energy saving and low carbon, excellent mechanical properties, digestible solid waste, and good heavy metal solidification effect. Therefore, the present invention is based on the principle of volcanic ash reaction, and uses a variety of solid wastes combined with water-washed and dechlorinated fly ash from the incineration of domestic waste to prepare high-strength, low-cost all-solid waste-based, unfired ceramsite.
[0006] Invention patent number CN115010419A proposes a multi-solid waste sludge-based carbon mineralized unburned ceramsite. The obtained ceramsite has a cylinder pressure strength of 5.1-6.2MPa and excellent strength. However, its raw materials contain cement, activator and dispersant, and it adopts CO2 high-pressure mineralization and 100°C high-temperature curing process, which increases the preparation cost and uses a large amount of carbon dioxide, which is not energy-saving and environmentally friendly. Invention patent number CN116239362A proposes a lightweight foam concrete unburned ceramsite. The lightweight ceramsite is prepared using desulfurized gypsum, iron tailings sand and composite admixtures. Its cylinder pressure strength is 2.18-2.56MPa and its bulk density is 560-580kg / m 3 , with the characteristics of light weight and thermal insulation, but cement, waterproofing agent, foam stabilizer, foaming agent and stimulant are also added in the preparation process, which increases the preparation cost, and the use of cement will produce a large amount of carbon dioxide, which is not energy-saving and environmentally friendly, and has low strength. Invention patent number CN115368041A proposes a variety of solid waste unburned ceramsite based on phosphogypsum, with a 21d cylinder pressure strength of 4.21-5.24MPa and a water absorption rate of 14.6%-19.8%. The preparation process is simple, but the phosphogypsum used needs to be fired at 180-260℃ for 2-4h, and the phosphorus tailings need to be calcined at 900-1200℃ for 3-6h, which increases the energy consumption generated by the preparation. The addition of water glass, silane coupling agent and other additives increases the preparation cost, which is not in line with the principle of green environmental protection, and the water absorption performance of ceramsite is not optimized enough. Summary of the invention
[0007] In order to solve the technical problem of environmental protection in the existing technology for preparing unfired ceramsite, the present invention provides a method for preparing all-solid waste-based unfired ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes. The method adopts specific raw materials and utilizes four solid wastes, namely, fly ash from thermal power plants, blast furnace granulated slag, flue gas desulfurization gypsum and domestic waste incineration fly ash after washing and dechlorination, without adding any admixtures. The method only needs natural curing at room temperature for a few days. The prepared all-solid waste-based unfired ceramsite has the excellent characteristics of high strength, low cost, easy preparation, no energy consumption and no carbon emission, and can digest a large amount of solid waste and effectively solidify the heavy metals in the dechlorinated domestic waste incineration fly ash. The method provides a new path for solving the problem of solidification / resource utilization of solid waste, especially dechlorinated domestic waste incineration fly ash, and truly achieves the purpose of environmental protection.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes, comprising the following steps:
[0010] Step 1: Material mixing:
[0011] Weigh and prepare materials according to the proportioning scheme: 20-45 parts of fly ash from thermal power plants: 35-55 parts of granulated slag from blast furnaces: 5-15 parts of flue gas desulfurization gypsum: 5-15 parts of domestic waste incineration fly ash after washing and dechlorination;
[0012] Step 2: preparing alkali-activated gel slurry:
[0013] The fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash are uniformly mixed, and then 35%±0.5% of pure water is added according to the dry weight of the powder, and the mixture is stirred to obtain the alkali-activated gelled slurry;
[0014] Step three, preparing the all-solid waste-based unfired ceramsite:
[0015] The alkali-activated gelled slurry is prepared into ceramsite weighing about 3.5 g ± 0.1 g, and naturally cured at room temperature for several days to obtain the all-solid waste-based unfired ceramsite.
[0016] As a further improvement of the above scheme, the chemical composition and mass fraction of the fly ash of the thermal power plant include: SiO2: 40% to 50%; Al2O3: 35% to 45%; Fe2O3: 3% to 6%; CaO: 2% to 3%; at least one of TiO2 and K2O: 2% to 4%.
[0017] As a further improvement of the above scheme, the chemical composition and mass fraction of the blast furnace granulated slag include: CaO: 37% to 47%; SO3: 15% to 23%; SiO2: 15% to 20%; Al2O3: 8% to 12%; Fe2O3: 3% to 5%; at least one of ZnO, PbO, CuO, and Cl: 1% to 3%.
[0018] As a further improvement of the above scheme, the chemical composition and mass fraction of the flue gas desulfurization gypsum include: CaO: 58% to 64%; SO3: 29% to 34%; CaO+SO3: >90%; SiO2: 2% to 4%; Al2O3: 2% to 3%; at least one of Fe2O3, K2O, Cl, and TiO2: 1% to 3%.
[0019] As a further improvement of the above scheme, the chemical composition and mass fraction of the domestic waste incineration fly ash after water washing and dechlorination include: CaO: 60%~75%; SO3: 7%~11%; Cl: 2%~4%; SiO2: 3%~5%; Al2O3: 0.6%~1.4%; at least one of Na2O, MgO, Fe2O3, K2O, ZnO, TiO2, PbO, CuO: 7%~11%.
[0020] As a further improvement of the above scheme, the fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash are respectively sieved through a 100-mesh sieve before the materials are mixed.
[0021] As a further improvement of the above scheme, when preparing the alkali-activated gelled slurry, the fly ash from the thermal power plant, the blast furnace granulated slag, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash are added to a mixer and stirred evenly, and then poured into a beaker after stirring evenly.
[0022] As a further improvement of the above scheme, when preparing the alkali-activated gel slurry, 35%±0.5% of pure water is added according to the dry weight of the powder, and the mixture is stirred at a low speed for 30 seconds and at a high speed for 60 seconds to obtain the alkali-activated gel slurry.
[0023] As a further improvement of the above scheme, natural curing is carried out at room temperature for seven days.
[0024] As a further improvement of the above scheme, the raw material ratio of the fly ash from the thermal power plant, the blast furnace granulated slag, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash by mass is: 20 parts: 45 parts: 10 parts: 5 parts.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention creatively prepares solid waste-based alkali-activated cementitious materials based on the concept of coordinated disposal of solid wastes, rationally calculates and deduces specific alkali-activated cementitious materials, and can provide a theoretical basis for the coordinated resource utilization of solid wastes, and then rationally formulates the best alkali-activated cementitious materials by utilizing the chemical components of different solid wastes. Based on the specific alkali-activated cementitious materials, no additives are added during the preparation process, and only a few days of natural curing at room temperature (optimally 7 days) are required to allow the prepared all-solid waste-based unfired ceramsite to have the excellent characteristics of high strength, low cost, easy preparation, no energy consumption, and no carbon emissions, truly achieving the purpose of environmental protection.
[0027] 2. The dechlorinated municipal solid waste incineration fly ash (D-MSWI FA) described in the present invention contains a large amount of heavy metals, and the all-solid waste-based unburned ceramsite can effectively fix the heavy metals in the D-MSWI fly ash, greatly increasing the proportion of its residue state, and is expected to become a new generation of green products for stabilizing the treatment of D-MSWI fly ash in a low-carbon and energy-saving manner.
[0028] 3. The present invention belongs to the field of collaborative resource utilization of solid waste, and prepares a low-carbon cementitious material, providing a means of reducing carbon emissions in the high-carbon emission construction field. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flow chart of a method for preparing all-solid waste-based unfired ceramsite provided in an embodiment of the present invention.
[0030] Figure 2 For reference Figure 1 The physical properties diagram of NSC (i.e. unburned ceramsite) crushing strength at different FA (i.e. fly ash from thermal power plants) dosage ratios is shown in the middle method.
[0031] Figure 3 For reference Figure 1 The physical properties diagram of NSC apparent density at different FA content ratios using the Chinese method.
[0032] Figure 4 For reference Figure 1 The variation of 1-hour water absorption rate and softening coefficient of NSC with different FA dosage ratios is shown in the figure.
[0033] Figure 5 For reference Figure 1 The physical properties diagram of NSC crushing strength under different GGBFS (i.e. blast furnace granulated slag) dosage ratios is shown in the figure.
[0034] Figure 6 For reference Figure 1 The apparent density physical properties diagram of NSC at different GGBFS dosage ratios using the Chinese method.
[0035] Figure 7 For reference Figure 1 The variation of 1-hour water absorption and softening coefficient of NSC with different GGBFS dosage ratios is shown in the figure.
[0036] Figure 8 For reference Figure 1 The physical properties diagram of NSC crushing strength under different FGDG (i.e. flue gas desulfurization gypsum) dosage ratios is shown in the middle method.
[0037] Fig. 9 For reference Figure 1 The apparent density physical properties diagram of NSC at different FGDG dosage ratios using the Chinese method.
[0038] Fig.10 For reference Figure 1 The variation of 1-hour water absorption rate and softening coefficient of NSC with different FGDG dosage ratios is shown in the figure.
[0039] Fig.11 For reference Figure 1 The physical properties diagram of NSC crushing strength under different D-MSWI FA (i.e., dechlorinated municipal solid waste incineration fly ash) dosage ratios is shown in the middle method.
[0040] Fig.12 For reference Figure 1 The apparent density physical properties diagram of NSC at different D-MSWI FA dosage ratios using the Chinese method.
[0041] Fig.13 For reference Figure 1 The variation of 1-hour water absorption and softening coefficient of NSC with different D-MSWI FA dosage ratios using the Chinese method.
[0042] Fig.14 Four ceramic raw materials and Figure 1 In this embodiment, there are a total of 6 XRD diffraction patterns of NSC at three-day and seven-day curing ages.
[0043] Fig.15 FTIR analysis spectra of the NSC prepared in Example 1 at three-day and seven-day curing ages.
[0044] Figure 16 to Figure 21 The scanning electron microscopy results of the NSC prepared in Example 1 at different points in 3d.
[0045] Fig. 22 This is the energy spectrum analysis scanning point diagram of the NSC prepared in Example 1 at 3d.
[0046] Fig.23 This is the energy spectrum analysis result of the NSC prepared in Example 1 at 3d.
[0047] Figure 24 to Figure 29 The scanning electron microscopy results of the NSC prepared in Example 1 at different points at 7 days.
[0048] Fig.30 This is the energy spectrum analysis scanning point diagram of the NSC prepared in Example 1 at 7 days.
[0049] Fig.31 This is the energy spectrum analysis result of the NSC prepared in Example 1 at 7 days. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] See also Figure 1 , which is a flow chart of a method for preparing all-solid waste-based unburned ceramsite provided by an embodiment of the present invention. The method for preparing all-solid waste-based unburned ceramsite belongs to a method for preparing all-solid waste-based unburned ceramsite by combining multiple solid wastes with dechlorinated domestic waste incineration fly ash, and the method is as follows.
[0052] Step 1: Material mixing: After passing the raw materials through a 100-mesh sieve, weigh and prepare the materials according to the ratio scheme: 20 parts of fly ash from a thermal power plant, 45 parts of granulated slag from a blast furnace, 10 parts of flue gas desulfurization gypsum and 5 parts of domestic waste incineration fly ash after washing and dechlorination.
[0053] The chemical composition and mass fraction of the fly ash from the thermal power plant can be as follows: SiO2 is 40% to 50%, Al2O3 is 35% to 45%, Fe2O3 is 3% to 6%, CaO is 2% to 3%, and others (TiO2, K2O, etc.) are 2% to 4%. The chemical composition and mass fraction of the blast furnace granulated slag can be as follows: CaO is 37% to 47%, SO3 is 15% to 23%, SiO2 is 15% to 20%, Al2O3 is 8% to 12%, Fe2O3 is 3% to 5%, and others (ZnO, PbO, CuO, Cl, etc.) are about 1% to 3%. The chemical composition and mass fraction of the flue gas desulfurization gypsum can be: CaO is 58% to 64%, SO3 is 29% to 34%, CaO+SO3>90%, SiO2 is 2% to 4%, Al2O3 is 2% to 3%, and others (Fe2O3, K2O, Cl, TiO2, etc.) are about 1% to 3%. The chemical composition and mass fraction of the domestic waste incineration fly ash after water washing and dechlorination can be: CaO is 60% to 75%, SO3 is 7% to 11%, Cl is 2% to 4%, SiO2 is 3% to 5%, Al2O3 is 0.6% to 1.4%, and others (Na2O, MgO, Fe2O3, K2O, ZnO, TiO2, PbO, CuO, etc.) are 7% to 11%.
[0054] In other embodiments, the materials can be weighed and prepared according to the proportioning scheme: 20 to 45 parts of fly ash from a thermal power plant: 35 to 55 parts of granulated slag from a blast furnace: 5 to 15 parts of flue gas desulfurization gypsum: 5 to 15 parts of domestic waste incineration fly ash after washing and dechlorination.
[0055] Step 2, prepare alkali-activated gelled slurry: add fly ash from a thermal power plant, granulated slag from a blast furnace, flue gas desulfurization gypsum and washed and dechlorinated domestic waste incineration fly ash into a mixer and stir evenly. After ensuring that they are stirred evenly, pour them into a beaker, and then add 35%±0.5% of pure water according to the dry weight of the powder, stir at a low speed for 30 seconds, and stir at a high speed for 60 seconds to obtain an alkali-activated gelled slurry.
[0056] In other embodiments, the fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash can be evenly mixed, and then 35%±0.5% of pure water is added according to the dry weight of the powder, and stirred to obtain the alkali-activated gelled slurry.
[0057] Step 3: Prepare unburned ceramsite: stir evenly the fly ash from thermal power plants, granulated slag from blast furnaces, flue gas desulfurization gypsum and washed and dechlorinated fly ash from domestic waste incineration to artificially prepare ceramsite weighing about 3.5g (±0.1g), and naturally cure it for seven days at room temperature to obtain the unburned ceramsite product. Its crushing strength is 5.94MPa and its apparent density is 1911kg / m 3, the water absorption rate in 1h is 3.12% and the softening coefficient is 68.47%.
[0058] In other embodiments, the alkali-activated gelled slurry can be prepared into expanded clay weighing about 3.5 g ± 0.1 g, and naturally cured at room temperature for several days to obtain the all-solid waste-based unfired expanded clay.
[0059] Compared with the traditional technology, the traditional technology uses P.M32.5 grade silicate cement in the same way, and the water-cement ratio is 28.5 to prepare the unburned ceramsite with a crushing strength of 3.08MPa and an apparent density of 2088kg / m 3 The water absorption rate in 1h is 9.46%, and the softening coefficient is 77.15%. Except for the slightly higher softening coefficient, the other physical properties are significantly lower than those of the all-solid waste-based unfired ceramsite prepared by the present invention.
[0060] The present invention creatively prepares solid waste-based alkali-activated cementitious materials based on the concept of solid waste collaborative disposal, and reasonably calculates and deduces specific alkali-activated cementitious materials (using four solid wastes, namely, fly ash from thermal power plants, granulated slag from blast furnaces, flue gas desulfurization gypsum, and domestic waste incineration fly ash after washing and dechlorination, for collaborative disposal), which can provide a theoretical basis for the collaborative resource utilization of solid waste, and then rationally formulate the best alkali-activated cementitious materials by using the chemical components of different solid wastes. Based on the specific alkali-activated cementitious materials, no additives are added during the preparation process, and only a few days (optimally 7 days) of natural curing at room temperature are required to allow the prepared all-solid waste-based unfired ceramsite to have the excellent characteristics of high strength, low cost, easy preparation, no energy consumption, and no carbon emissions, truly achieving the purpose of environmental protection, and being able to digest a large amount of solid waste and effectively solidify the heavy metals in the dechlorinated domestic waste incineration fly ash, providing a new path for solving the solidification / resourceization problem of solid waste, especially dechlorinated domestic waste incineration fly ash, under the "dual carbon" goal.
[0061] See the four groups of pictures, the first group of pictures: Figure 2 , 3 , 4, the second group of pictures: 5, 6, 7, the third group of pictures: 8, 9, 10, the fourth group of pictures: 11, 12, 13. Among them, Figure 2 For reference Figure 1 The physical properties diagram of crushing strength of NSC (i.e. unburned ceramsite) at different FA (i.e. fly ash from thermal power plant) content ratios by the middle method; Figure 3 For reference Figure 1 The physical properties diagram of NSC apparent density at different FA content ratios by the middle method; Figure 4 For reference Figure 1 The variation of 1-hour water absorption rate and softening coefficient of NSC with different FA dosage ratios is shown in the figure. Figure 5 For reference Figure 1The physical properties diagram of NSC crushing strength under different GGBFS (i.e. blast furnace granulated slag) dosage ratios by the middle method; Figure 6 For reference Figure 1 The physical properties diagram of NSC apparent density at different GGBFS dosage ratios by the middle method; Figure 7 For reference Figure 1 The variation of 1-hour water absorption and softening coefficient of NSC with different GGBFS dosage ratios is shown in the figure. Figure 8 For reference Figure 1 The physical properties diagram of NSC crushing strength under different FGDG (i.e. flue gas desulfurization gypsum) dosage ratios in the middle method; Fig. 9 For reference Figure 1 The physical properties diagram of NSC apparent density at different FGDG content ratios by the middle method; Fig.10 For reference Figure 1 The variation of 1-hour water absorption rate and softening coefficient of NSC with different FGDG dosage ratios is shown in the figure. Fig.11 For reference Figure 1 The physical properties diagram of NSC crushing strength under different D-MSWI FA (i.e., dechlorinated municipal solid waste incineration fly ash) dosage ratios by the middle method; Fig.12 For reference Figure 1 The physical properties diagram of NSC apparent density at different D-MSWI FA dosage ratios by the middle method; Fig.13 For reference Figure 1 The method in the middle shows the variation of the water absorption rate and softening coefficient of NSC in one hour with different D-MSWI FA dosage ratios. It can be seen that among the experimental groups with different dosage ratios of different ceramic raw materials, the comprehensive performance of the experimental group with FA dosage: base material = 4:12 is the best, that is, the ratio of this example is the best ratio.
[0062] See also Fig.14 It can be seen that there is an obvious diffusion peak between 20 and 40° in NSC, indicating that amorphous gel products are generated, and it becomes more obvious with the increase of curing age, proving that the hydration reaction continues and the gel products increase further. Sodium chloride contained in fly ash and mullite in fly ash are not found in NSC. It may be that these substances are decomposed into gel products, ettringite and other substances in the hydration reaction or are wrapped inside the gel products.
[0063] See also Fig.15 From the infrared spectra of NSC-3d and NSC-7d, we can see that the group peaks of the two are the same, indicating that the composition of the material has not changed over time. -1 The peak at 1650cm is the stretching vibration absorption peak of OH in the crystal water of desulfurized gypsum. -11423cm is the bending vibration absorption peak of OH in the crystal water of desulfurized gypsum, indicating that with the increase of curing age, the hydration reaction continues, the number of hydration products increases, and the content of hydroxyl in the system increases. -1 The peak at 1112cm is the stretching vibration absorption peak of carbonate, indicating that the sample reacted with CO2 in the air during the sample preparation process and carbonized (11). -1 The antisymmetric stretching vibration absorption peak of Si-O in fly ash and MSWI fly ash and the antisymmetric stretching vibration absorption peak of sulfate in desulfurized gypsum are 956 cm -1 The bending vibration absorption peaks of Si-OH in fly ash and MSWI fly ash are both enhanced with the increase of curing age, indicating that more Si-O-Al bonds are broken in the early stage and participate in the reaction to generate AFt, and the number is gradually increasing. The continuous sharpening indicates that various silicate minerals in the system are consumed, and the total amount of CSH gel is increasing. -1 The bending vibration absorption peak of carbonate is 448 cm -1 The MO (M in fly ash and MSWI fly ash) is the stretching vibration absorption peak of Al, Fe, and Ca metal oxides, which is also the characteristic peak of CSH gel.
[0064] Figure 16-21 is the scanning electron microscope result of sample 3d, and 22 and 23 are the element spectrum scanning results of sample 3d. Fig.16 As shown in the figure, at a scale of 20um, it can be seen that the hydration process of gypsum proceeds rapidly, the surface of the spherical fly ash particles is rough, and is covered with a layer of dense reaction product CSH gel. At the same time, there are a large number of blocky objects on the surface, which are residual mineral powders. Other fine particles are a mixture of fly ash and FDG. A large number of local CSH also tightly wraps these incompletely hydrated raw materials. It can be seen that the initial hydration speed of the mineral powder is low, and only a small amount of minerals undergo hydration reaction. With the OH in the solution, - and Ca 2+ As the concentration increases, the mineral powder also begins to undergo hydration reaction. At the same time, FDG can act as a catalyst to stimulate the activity of the mineral powder and promote the hydration reaction. Fig.17 As shown in the figure, at the scale of 10um and 5um, it can be seen that in addition to the raw materials, obvious rod-shaped AFt is also produced, but the distribution is relatively loose, and there are still relatively large pores between them after being combined by CSH gel, indicating that the porosity is large at this time and the mechanical strength of the material is weak. Fig.18 As shown in the figure, although the hydration product CSH gel will adsorb and wrap on the surface of the raw material, improve stability and fill certain pores, increase structural density and increase water resistance, due to the short hydration time, a large part of unhydrated mineral particles still exist on the surface. Fig.19As shown, there are small pieces of dense rod-shaped AFt on the surface, and the particles are interlocked with each other and wrapped by CSH gel to form a network structure. At the same time, a small amount of flake AFm also appears. Fig. 20 , 21 It is shown that the product formed is basically consistent with the above-mentioned product, indicating that the product distribution formed by the raw material is highly consistent.
[0065] Fig. 22 , 23 As shown in the figure, the element distribution area is mainly distributed with obvious AFt and AFm, and CSH gel wraps them together. AFt and AFm are mainly composed of a large amount of Ca and a small amount of Al. At the same time, the particles with higher activity quickly dissolve in the alkaline environment of FGDG, forming a large amount of OH - , Ca 2+ , silicon-aluminum dissolved substances, causing the Si-O bonds and Al-O bonds therein to break continuously, which corresponds to the 64.94% Ca, 10.33% Al, 65.97% Ca, and 10.00% Al in the EDS results. At the same time, there is about 17% Si corresponding to the characteristic elements of CSH gel. The EDS analysis results are consistent with the SEM analysis results. Although there is obvious CSH gel in sample 3d that wraps the surface of the material to prevent gypsum from dissolving and form a tight and solid structure of the hardened body, there are still some microcracks and incompletely hydrated mineral particles and fly ash.
[0066] Figure 24-29 30 and 31 are the scanning electron microscope results of sample 7d, and 31 and 32 are the element spectrum scanning results of sample 7d. Fig.24 As shown in the figure, at a scale of 20 μm, it can be seen that as the mixture of GGBFS, FGDG and FA continues to hydrate, more CSH gel is generated, which basically covers the surface of the sample, greatly improving the density of the sample, thereby improving the mechanical strength. The large reduction in spherical particles also shows that the FA is basically disintegrated and replaced by a large number of reaction products. Fig.25 As shown in the figure, at the scale of 10um and 5um, it can be seen that after 7 days of hydration, a very small amount of AFm and sparse Aft are generated. This is because the Aft crystals generated early broke the dissolution equilibrium of the glass phase in the mineral powder, causing the Si-O bonds in it to dissociate and generate H2SiO4 2- , and then react with Ca in alkaline solution 2+ The reaction generates CSH gel, and the active substances released in this process can promote the gel reaction, increase the activity of fly ash, and improve the strength and durability of the sample. A large number of aggregated oblate spherical particles AH3 are generated by the reaction of Al2O3 in fly ash and Ca(OH)2. AH3 can improve the chemical stability of the sample. Fig.26 , 27 , 28It can be seen that the large mineral particles are significantly reduced, and the generated CSH gel is more compact, which wraps the generated hydration products and incompletely hydrated raw materials, fills most of the pores on the surface, and reduces the surface roughness of the sample. Fig.29 As shown in Figure 3, cracks appeared on the surface of the microstructure, which was caused by the expansion of Aft, but the generated fine CSH gel filled this part.
[0067] Fig.30 The EDS results show that the 7d hydrated sample is a silicon-rich substrate, suitable for the growth of CASH phase, accompanied by other secondary minerals, such as Aft. In the silicon-rich area, it can be clearly seen that thin and long fibers grow out of the formed shell, and the ends of the fibers are accompanied by some nodules, which are obvious CASH structures. In addition, wood-board / thick-rod-shaped Aft secondary minerals are generated nearby, such as Fig.30 , 31 As shown, Fig. 22 , 23 Compared with the 3d sample shown, Ca is reduced by about 40% and Si is increased by about 20%, which clearly indicates the increase of CSH. At the same time, the fine gel-like objects in the microstructure also fully illustrate this point. The consumption of various silicate minerals in the system increases, and the total amount of CSH gel is increasing. Compared with the amorphous gel in 3d, the CSH in 7d is obviously much tighter and denser. At the same time, this may also be that the active aluminum silicate in MSWI fly ash and some substances in fly ash can participate in chemical reactions during the hydration process to form some new substances, such as AH3, a more dense structure. At the same time, the large increase in Al also shows that the continued hydration generates AH3, a hydration product.
[0068] It can be seen that there are a large number of gel products and strength structures such as calcium sulfonite on the surface of NSC, and the pores are gradually filled with the increase of age to increase the crushing strength. From the EDS results, it can also be seen that the proportion of Si-Al structure on the surface of NSC has increased significantly. Some fly ash, fly ash, and mineral powder are dissolved by desulfurized gypsum and participate in the hydration reaction. The heavy metals in them are solidified by generating sulfides, hydroxides, complexes, etc. in the hydration system; the SEM image shows that there are still some unreacted fly ash, fly ash, and mineral powder particles. These fine particles are wrapped in the gel product, indicating that NSC can also prevent heavy metal leaching by physical wrapping.
[0069] As shown in Table 1, the leaching concentration of heavy metals in NSC is significantly lower than the limit value of the Integrated Wastewater Discharge Standard (GB8978-1996), and it is an applicable environmentally friendly material.
[0070] Table 1 Example 1 NSC leaching situation table
[0071]
[0072] GB8978—1996 Comprehensive sewage discharge standard
[0073] In order to better prove that the present invention has indeed achieved: "solving the problem of solidification / resource utilization of solid waste, especially dechlorinated domestic waste incineration fly ash under the 'dual carbon' goal, providing a new path, and truly achieving the purpose of environmental protection", the present invention has conducted 21 groups of experiments (such as Figure 2-5 ), and 5 groups of experiments are listed as shown in Table 2.
[0074] Table 2 Characteristics of all-solid waste-based unburned ceramsite at different ratios
[0075]
[0076]
[0077] As can be seen from Table 2, the present invention is mainly based on the preparation method of all-solid waste-based unfired ceramsite, and the all-solid waste-based unfired ceramsite is synthesized on the principle of combining dechlorinated domestic waste incineration fly ash with a variety of solid wastes, providing a low-carbon stabilization and resource utilization approach for dechlorinated domestic waste incineration fly ash, making up for the shortcomings of mineral resource consumption and high carbon emission problems caused by fly ash cement-based solidification / stabilization and cement production itself. Compared with the ceramsite made of PSA32.5 grade cement, it has the characteristics of high strength, light weight and low water absorption. The all-solid waste-based unfired ceramsite prepared by a reasonable formulation (this embodiment) can reach a strength of 5.94MPa and an apparent density of 1911.0kg / m after natural curing for seven days at room temperature. 3 , the water absorption rate in 1h is 3.12% and the softening coefficient is 68.47%.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes, characterized in that: It includes the following steps: Step 1: Material mixing: Weigh and prepare materials according to the proportioning scheme: 20-45 parts of fly ash from thermal power plants: 35-55 parts of granulated slag from blast furnaces: 5-15 parts of flue gas desulfurization gypsum: 5-15 parts of domestic waste incineration fly ash after washing and dechlorination; Step 2: preparing alkali-activated gel slurry: The fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash are uniformly mixed, and then 35%±0.5% of pure water is added according to the dry weight of the powder, and the mixture is stirred to obtain the alkali-activated gelled slurry; Step three, preparing the all-solid waste-based unfired ceramsite: The alkali-activated gelled slurry is prepared into ceramsite weighing about 3.5 g ± 0.1 g, and naturally cured at room temperature for several days to obtain the all-solid waste-based unfired ceramsite.
2. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: The chemical composition and mass fraction of the fly ash from the thermal power plant include: SiO2: 40%~50%; Al2O3: 35%~45%; Fe2O3: 3%~6%; CaO: 2%~3%; At least one of TiO2 and K2O: 2% to 4%.
3. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: The chemical composition and mass fraction of the blast furnace granulated slag include: CaO: 37%~47%; SO3: 15%~23%; SiO2: 15% to 20%; Al2O3: 8%~12%; Fe2O3: 3%~5%; At least one of ZnO, PbO, CuO, and Cl: 1% to 3%.
4. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: The chemical composition and mass fraction of the flue gas desulfurization gypsum include: CaO: 58%~64%; SO3: 29%~34%; CaO+SO3:>90%; SiO2: 2%~4%; Al2O3: 2%~3%; At least one of Fe2O3, K2O, Cl, TiO2: 1% to 3%.
5. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: The chemical composition and mass fraction of the domestic waste incineration fly ash after water washing and dechlorination include: CaO: 60%~75%; SO3: 7%~11%; Cl:2%~4%; SiO2: 3%~5%; Al2O3: 0.6%~1.4%; At least one of Na2O, MgO, Fe2O3, K2O, ZnO, TiO2, PbO, CuO: 7% to 11%.
6. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: The fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash are respectively sieved through a 100-mesh sieve before the materials are mixed.
7. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: When preparing the alkali-activated gelled slurry, the fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash are added into a mixer and stirred evenly, and then poured into a beaker after being stirred evenly.
8. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: When preparing the alkali-activated gel slurry, 35%±0.5% of pure water is added according to the dry weight of the powder, and the mixture is stirred at a low speed for 30 seconds and at a high speed for 60 seconds to obtain the alkali-activated gel slurry.
9. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: Natural curing at room temperature for seven days.
10. The method for preparing all-solid waste-based unburned ceramsite by combining dechlorinated domestic waste incineration fly ash with multiple solid wastes as claimed in claim 1, characterized in that: The raw material ratio by mass of the fly ash from the thermal power plant, the granulated slag from the blast furnace, the flue gas desulfurization gypsum and the dechlorinated domestic waste incineration fly ash is: 20 parts: 45 parts: 10 parts: 5 parts.
Citation Information
Patent Citations
Multi-solid-waste non-sintered ceramsite based on phosphogypsum and preparation method of multi-solid-waste non-sintered ceramsite
CN115368041A
Lightweight foam concrete unfired ceramsite and preparation method thereof
CN116239362A
Treatment method for synergistically curing waste incineration fly ash by using silicon-aluminum-based cementing material
CN118026605A
Domestic waste incineration fly ash-based geopolymer composite unfired granular material and preparation method thereof
CN118145900A
Cited By
Waste incineration fly ash all-solid waste high-strength artificial aggregate preparation method based on disc granulation
CN122325137A
A method for preparing a full-solid waste high-strength artificial aggregate of waste incineration fly ash based on disc granulation
CN122325137B